Araceae Floristic and Potential Study in Bogor Botanical Gardens, West Java, Indonesia - Asharo, Rizal Koen; Novitasari, Ayu; Azizah, Sri Devi Nur; Saraswati, Rahadian Ajeng; Setyaningsih, Fani; Apriliani, Puput; Priambodo, Rizky; Pasaribu, Pinta Omas; Rizkawati, Vina; Usman, Usman (Jurnal Riset Biologi dan Aplikasinya, 2022)
Bogor Botanical Gardens is a conservation area that assists the preservation of flora in Indonesia, including the Araceae. Araceae is often used by the public as medicine, food sources, and ornamental plants. Therefore, the Araceae is often used as an interesting research object and conservation efforts have commenced maintaining its sustainability. The purpose of this research was to determine the species of living Araceae and the potential possessed by each living Araceae species in the conservation area of the Bogor Botanical Gardens. This research was conducted on 8-9 June 2021 to determine the diversity and potential of the Araceae in Bogor Botanical Gardens. The method used in this research is the exploring method and data analysis using descriptive method. The result of this research revealed there were 60 species of Araceae consisting of 25 genera. The genera with the highest number of species are Philodendron. Two species of them are Araceae which has a habitat in the waters. A total of 33 species are terrestrial and 25 are epiphytic plants. Araceae have many potentials, such as food, aromatic, medicine, flavoring, animal feed, and ornamental plants. More than 50% of the Araceae species were used as ornamental plants.